Benefit of endoscopic stenting for dominant strictures in patients with primary sclerosing cholangitis - Han, Samuel; Shah, Raj J. (Endoscopy International Open, 2022)
Background and study aims Dominant strictures (DS) occur in up to 60 % of patients with primary sclerosing cholangitis (PSC). Data regarding the long-term effects of stenting vs. dilation remain limited. The aim of this study was to compare the two treatment modalities in terms of transplantation-free survival.Patients and methods This single-center, retrospective study examined patients with PSC and DS treated endoscopically with a minimum of 1 year follow-up. Patients were divided into two cohorts: 1) those who received dilation alone; and 2) those who received both dilation and stenting. The primary outcome was transplantation-free survival, defined as time after index ERCP to liver transplantation.Results In all, 169 patients (54 in dilation cohort, 115 in stenting cohort) were included. The stenting cohort had a significantly higher Mayo PSC Risk Score (1.8 ± 1.1 vs. 0.9 ± 1.2) and presented with cholangitis more frequently (22.6 % vs. 1.9 %). During a follow-up period of 1198 person-years, 69 (40.8 %) patients received transplantation at a mean of 3.4 (± 2.9) years. There was no difference in transplantation rate in the stenting cohort [68 (95 % CI 5.2–8.8) per 100 person-years] compared to the dilation cohort [3.7 (95 % CI 2.1–6.0) per 100 person-years] and no difference in risk for transplantation (dilation cohort adjusted hazards ratio 0.67, 95 % CI 0.33–1.32).Conclusions Despite a higher Mayo Risk Score in the stenting group, there was no difference in transplantation-free survival between patients managed with stenting vs. dilation alone. Stenting, therefore, may offer benefit in patients with advanced PSC and DS.